2014
DOI: 10.1016/j.adolescence.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Father absence and timing of menarche in adolescent girls from a UK cohort: The mediating role of maternal depression and major financial problems

Abstract: In a prospective birth cohort study of 5295 girls from the UK‐based Avon Longitudinal Study of Parents and Children (ALSPAC), we examined the association between biological father absence in childhood and age at menarche whilst adjusting for antenatal indicators of socioeconomic disadvantage and maternal characteristics. We also examined whether exposure to maternal depression and financial problems during middle childhood mediate the association between father absence and age at menarche. There was stronger e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 69 publications
3
43
0
Order By: Relevance
“…Lack of paternal influence and quality of the paternal relationship during early childhood has been linked with early menarche [102][103][104][105][106]. One study found that the first five years of life were the most critical for paternal influence to be protective against early menarche [104]. Another study found that it was not paternal absence, but the lack of a quality relationship with one's father that was linked with early menarche [106].…”
Section: Disease Causes and Consequencesmentioning
confidence: 99%
“…Lack of paternal influence and quality of the paternal relationship during early childhood has been linked with early menarche [102][103][104][105][106]. One study found that the first five years of life were the most critical for paternal influence to be protective against early menarche [104]. Another study found that it was not paternal absence, but the lack of a quality relationship with one's father that was linked with early menarche [106].…”
Section: Disease Causes and Consequencesmentioning
confidence: 99%
“…Although both theories place different emphasis on the role of fathers influencing the timing of pubertal maturation in girls, they converge on the assumption that stressful early childhood experiences, including father absence, affect the physiological and hormonal mechanisms that initiate and control pubertal development (Ellis 2004). The accelerating effect of father absence on subsequent timing of menarche has been consistently reported across a range of cross-sectional (Bogaert 2008; Romans et al 2003; Quinlan 2003) and longitudinal studies (Belsky et al 2007; Culpin et al 2014; Ellis and Garber 2000). In addition, there is evidence to suggest that exposure to father absence during the first 5 years of life is more strongly associated with early menarche than father absence later in childhood (Alvergne et al 2008; Culpin et al 2014; Moffitt et al 1992).…”
mentioning
confidence: 87%
“…Girls who grow up in households from which their biological father is absent are consistently observed to experience menarche at younger ages as compared to peers with present fathers (Alvergne et al 2008;Bogaert 2008;Culpin et al 2014;Hoier 2003;Quinlan 2003). Father absence is also associated with subsequent reproductive timing; girls with absent fathers have younger age of first sex, pregnancy, and birth (Anderson 2015;Ellis et al 2003;Kiernan and Hobcraft 1997;Mendle et al 2009;Moffitt et al 1992).…”
Section: Father Absence and Early Pubertymentioning
confidence: 99%